A compact, lightweight, variable-energy cyclotron for conventional and FLASH ion beam radiotherapy - Winklehner, D.; Minervini, J. V.; Bromberg, L.; Forton, E.; Mandrillon, J.; Michael, P. C.; Radovinsky, A. (Frontiers in Oncology, 2025)
IntroductionThe advantage of ion beam radiotherapy for cancer lies in its low dose proximal and distal to the tumor, owed to an energy-dependent depth-dose profile, the Bragg-peak. However, conventional techniques to achieve different energies often rely on degraders, which compromise the quality and intensity of the beam and produce secondary radiation.MethodsWe propose a novel conceptual design for a compact accelerator capable of delivering ion beams (e.g., protons or carbon ions) with variable energy from 70 to 230 MeV/amu. Removing all magnetic iron from the device yields a linear relationship between coil current and cyclotron magnetic field, and, thus, smooth scaling of the output beam energy. We base our findings on finite elements calculations, particle ray-tracing and particle-in-cell simulations.ResultsIn the absence of magnetic iron, we achieve a much lighter system with improved magnetic shielding and significantly reduced secondary radiation that can provide ion beams at variable energy while providing the high beam intensity necessary for the promising FLASH technique at all output energies.DiscussionThis design represents a promising advancement in ion beam radiotherapy, combining energy flexibility, reduced radiation hazards, and compatibility with high-intensity techniques. It may pave the way for more efficient, compact, and clinically versatile accelerator systems.